The first Australian experience with ward‐based continuous positive airway pressure for COVID‐19 respiratory failure: a retrospective cohort study. Issue 11 (3rd November 2022) - Gerhardy, Benjamin; Comsa, Monica; Tahir, Ali; Lynch, Dalton; Polkinghorne, Adam; Orde, Sam; Branley, James; Morgan, Lucy
Abstract: We present the first Australian cohort of patients with COVID‐19 respiratory failure managed with escalating respiratory support including continuous positive airway pressure (CPAP) on a standard medical ward at a tertiary Sydney hospital during the 2021 COVID‐19 Delta variant outbreak. We demonstrate an equivalent mortality to CPAP delivered in intensive care unit and outline our ward structure and management during the pandemic.